Job Satisfaction Mediated the Predictive Relationship Between Leadership Behaviors and Turnover Intention among Civil in Cambodia: Focusing on One Window Service Offices - Mengtry Taing; Sarom Mok; Sothea Lim; Mengheang Hor (Riviera Publishing, 2026)
The subjects of toxic leadership, staff turnover intentions, and job satisfaction have drawn a lot of attention over time, providing scholars and organizations with tactics and insights for change, but excluding Cambodia. In doing so, this quantitative non-experimental study aimed to determine if and to what degree job satisfaction mediated the predictive association between toxic leadership behaviors and staff turnover intention among government servants at One Window Service Offices (OWSOs) in Cambodia. This study was guided by three theoretical frameworks: the theory of planned behavior, the motivation-hygiene theory, and the toxic triangle model. The Toxic Leadership Scale (TLS) was used to measure the predictor variable, toxic leadership behaviors; the Turnover Intention Scale (TIS-6) was used to measure the criterion variable, employee turnover intention; and the Job Satisfaction Survey (JSS) was used to measure the mediating variable, job satisfaction. A total of 111 OWSO civil servants participated in this study. The association between the predictor and criterion variables for Research Question One was examined using a multiple linear regression. The mediating effect of job satisfaction on the connection between the predictor and criterion variables for Research Question Two was tested using the Hayes PROCESS macro. Toxic leadership behaviors were found to be a significant predictor of turnover intentions (B = 0.473, p <.001). Because the 95% bootstrap confidence interval did not include zero [BootLLCI = 0.0006, BootULCI = 0.0304], PROCESS findings suggested that work satisfaction mediated this association.